Exploring the Protective Effects of Xueshuantong Injection on Central Retinal Vein Occlusion - Qiang Chen; Jing Zhang; Xin-Yu Liu; Kai Xu; Hui-Yi Guo; Ya-Min Li; Yu-Qing Guo; Li-Na Liang (World Journal of Traditional Chinese Medicine)
Objective: This study aimed to assess the therapeutic effects of Xueshuantong (XST), a traditional Chinese medicine that has been studied for its protective effects on the cardiovascular system and anti-inflammatory properties, on central retinal vein occlusion (CRVO) in rabbits and rats. Materials and Methods: CRVO was induced in rabbits and rats by laser photocoagulation. The animals were then treated with different doses of XST or lyophilized XST (L). Color fundus photography, fundus fluorescein angiography, histological examination, TUNEL assay, and immunofluorescence staining were conducted to evaluate the therapeutic effects. Results: The study revealed that both XST and lyophilized XST injections exhibited therapeutic effects against CRVO in rabbits and rats. The drugs improved retinal lesions and structure and mitigated apoptosis of retinal cells to varying degrees. Additionally, downregulation of tumor necrosis factor-α and interleukin-6 within the retina was observed in both drug groups. Conclusions: The results indicate that XST injection exhibited significant protective effects against experimental CRVO by regulating angiogenesis and inflammation, suggesting its potential as an effective therapeutic strategy for treating CRVO.